Validation of a Spanish language adaptation of the Scale for Socioemotional Competence for Teachers - Monzalvo Curiel, Alicia (Consorcio de Universidades Mexicanas A.C., 2019)
Socioemotional competence in teachers or the ability to regulate emotions according to social context is an important factor that influences academic motivation and helps the creation of inclusive classrooms. It is well known that cognitive abilities are important for adaptation to difficult situations; however, there is a dearth of research focusing on social and emotional aspects. There are limited instruments that can be used to assess socioemotional emotional competence in educational contexts and the few that exist were developed outside of Mexico and have not been validated in this context. Due to the high impact of teacher socioemotional competence on the social, emotional and intellectual development of students, it is important to have well-validated instruments to ensure correct measurement. To address this problem, we translated the Socio-Emotional Competency Teacher Evaluation Scale (SECTRS). In a sample of teachers (n = 222) its reliability and construct validity were evaluated and its factorial structure was investigated. Confirmatory factor analysis demonstrated that a 4-factor model with a second-order factor achieved acceptable goodness of fit. In congruence with previous literature, a negative correlation was found with an exhaustion factor and a positive correlation resulted with personal accomplishment and cultural sensibility. Our results will hopefully help the understanding of teacher socioemotional competence in Mexico and the development of better educational models and conditions.